열기계적 분석법으로 측정된 레진 포뮬레이션의 경화 수축 특성 - 서안나; Ahn Na Seo; 이종현; Jong Hyun Lee (대한금속·재료학회지, 50(9), 2012)
Volume shrinkage behavior accompanying the cure of resin formulations might be a critical factor when assembly processes using polymer materials are considered. In this study, cure shrinkage behavior with respect to resin formulation type and heating method was measured on sandwich structure samples by a thermomechanical analyzer (TMA). Quartz, used as a cover material for the sandwich structure, indicated the coefficient of thermal expansion close to 0 ppm/℃. When a dynamic heating mode was conducted, a squeezeout region and a cross-linking region for each resin formulation could be separated clearly with overlapping differential scanning calorimeter results on the TMA results. In addition, a cure shrinkage dominant region and a thermal expansion dominant region in the cross-linking region were distinguished. Consequently, the degree of cure at the initiation of the thermal expansion dominant region was successfully measured. Measurement of all resin formulations indicated the thermal expansion behavior exceeded cure shrinkage before full cure.